How to make your child safe in viral pandemic - Dutta, Juhi; Nandy, Arnab; Mondal, Rakesh (Indian Journal of Child Health, 2020)
The current coronavirus (CoV) disease-19 pandemic has taken the entire world to hell and back. While we are more focused on the containment of this virus from further spreading, there are certain imperceptible challenges which are gradually raging upfront to affect the overall child health. If they are not understood appropriately overtime, it can result into deleterious sequels in near future. The tangible effects of this viral pandemic also deserve similar attention alongside exploring the pathophysiology of medical illnesses caused by severe acute respiratory syndrome–CoV-2. A practical approach to address these issues has been discussed here considering “the new normal” as the future lifestyle.